Transanal endoscopic microsurgery: an indispensable component of contemporary coloproctology - Vavra, Petr; Andel, Petr; Pelikan, Anton; Martinek, Lubomir; Gunkova, Petra; Gunka, Igor (Lietuvos chirurgija, 2005)
Petr Vavra, Petr Andel, Anton Pelikan, Lubomir Martinek, Petra Gunkova, Igor Gunka Department of Surgery University Hospital of Ostrava, Ostrava-Poruba, 17. listopadu 1790, 708 52 Ostrava, Czech Republic E-mail: p_vavra@quick.cz Background / objective At many surgical and gastroenterological working places still persists the problem what to do with an adhered tumour in the rectum at an unfavourable distance from the anus. This paper presents the possibilities offered by contemporary coloproctology by means of TEM (transanal endoscopic microsurgery) applied to the lesions that are hardly accessible. Patients and methods At the Department of Surgery of University Hospital Ostrava, the TEM method has been used since August 2002. The technique itself was implemented by Buess in the year 1983. His working place in Tübingen, Germany serves also as a training centre for teaching TEM. In the Czech Republic, the TEM method was used for first time in 1992. In TEM methodology the advantages of mini-invasive endoscopic medical help and the advantages of surgical treatment are combined. Results At the Department of Surgery of University Hospital of Ostrava in the period between 01/2003 and 12/2003 we carried out 37 operations by means of TEM. Of this number, 15 patients were operated on for benign rectum affection, 18 for malign disease, other 4 operations were twice on periproctal fistula, one operation for rectum stenosis, one introduction of a self-expandible stent. In malign rectum lesions we performed CT and endosonography preoperatively and used TEM twice for carcinoma in situ, 6 times for T1NXM0 lesions, 3 times for T2NXM0 lesions and 4 times for T3NXM0 lesions. These patients were then operated on transabdominally on the basis of definite histological findings. For a palliative effect we used TEM twice in patients with metastatic liver affection T3NXMl and once for a patient with T4NXMl. Conclusions The TEM methodology introduced in 2002 has become an inseparable and inevitable component of coloproctological operations at our department. We think the main contribution of this method consists in a safe treatment of wide benign rectum lesions, in treatment of early rectal carcinoma stages, and last but not least, the use of TEM in palliative surgery of rectum while emphasising the quality of life preservation. Keywords: transanal endoscopic microsurgery, TEM unfavourable distance, indication, harmonic scalpel